IL-10 regulates adult neurogenesis by modulating ERK and STAT3 activity - Pereira, Leticia; Font-Nieves, Miriam; Van den Haute, Chris; Baekelandt, Veerle; Planas, Anna M.; Pozas, Esther (Frontiers in Cellular Neuroscience, 2015)
The adult SVZ contains Nestin+ progenitors that differentiate mainly into neuroblasts. Our previous data showed that IL-10 regulates SVZ adult neurogenesis by up-regulating the expression of pro-neural genes and modulating cell cycle exit. Here we addressed the specific mechanism through which IL-10 carries out its signaling on SVZ progenitors. We found that, in vitro and in vivo, IL-10 targets Nestin+ progenitors and activates the phosphorylation of ERK and STAT3. The action of IL-10 on Nestin+ progenitors is reversed by treatment with a MEK/ERK inhibitor, thus restoring neurogenesis to normal levels. Silencing STAT3 expression by lentiviral vectors also impaired neurogenesis by blocking the effects of IL-10. Our findings unveil ERK and STAT3 as effectors of IL-10 in adult SVZ neurogenesis.